Determinants of Crime in Chicago - Olson, Ross (2014)
This paper addresses occurrences of violent crime and their determinants in the city of Chicago using data collected at daily intervals for a period of two years. The economics of crime, in particular the price that crime imposes on society, is briefly explored along with a discussion of general policy techniques that aim to reduce the occurrence of violent crime. The empirical analysis addresses temperature, holidays (both official federal holidays and informal party holidays), weekends, unemployment rate, and seasonal trends. Relationships are examined between these variables and total crime, as well as with each component of violent crime: aggravated assault, sexual assault, robbery, and murder. It is hypothesized that through analyzing these independent variables and reacting accordingly by implementing change in policy, especially through increasing police presence, crime would likely be deterred to a greater extent